R&D collaboration with uncertain intellectual property rights - Dirk Czarnitzki; Katrin Hussinger; Cédric Schneider (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
Patent pendencies create uncertainty in research and development (R&D) collaboration agreements, resulting in a threat of expropriation of unprotected knowledge by potential partners, reduced bargaining power and enhanced search costs. In this paper, we show that - depending of the type of partner - uncertain intellectual property rights (IPR) lead to reduced collaboration between firms and may hinder the production of knowledge. This has implications for technology policy as R&D collaborations are exempt from anti-trust legislation in order to increase R&D in the economy. We argue that a functional IPR system is needed for successful utilization of this policy.
urn:nbn:de:bsz:180-madoc-31383
Keywords: O31; O38; 330; R&D collaboration; intellectual property; uncertainty; patents